A Role for World Languages in Improving Maine’s Economic Climate - Smith, Jane (Maine Policy Review, 2015)
Jane Smith argues that languages must be a fundamental component in educating Mainers for the global society of the twenty-first century. The article provides a brief overview of the state of world language education in Maine’s K–12 schools and post-secondary institutions and offers suggestions for steps we can take to increase the number of proficient speakers of other languages.